Designing for learning - An overview and evaluation of the Swedish school building history combined with strategies for designing schools. - Larsen, Ellinor (My University, 2023)
The Swedish school system has been described as experimenting with children. The criticism is mainly that new systems and pedagogical ideas were implemented quickly without being based on research. Have architects also treated the school building experimentally without reflecting on the potential consequences of their design? The aim of the thesis is to develop design strategies that promote learning that can be used when designing school environments. My goal is that the master thesis could be used by architects to get a better understanding of how school buildings should be designed in order to optimize learning and avoid repeating the mistakes found in historical examples. My research question have been: How should we design schools to promote learning according to research and evaluation of historical building typologies? To accomplish the aim and answer the research question, I reviewed research on school design linked to academic performance. Then, I analyzed historical school buildings by comparing them to the research. Thereafter, I designed two classrooms and adjacent group rooms, translating the research into design. Lastly, the literature review and historical analysis was concluded into design strategies aimed to guide architects to design schools that promote good academic performance. Research shows that lighting, color, material and room shape has a great impact on students’ behavior. Knowing how students are affected by our design choices is crucial when creating the right environment for the right task. The result of the historical evaluation shows that there has been a lack of understanding childrens’ needs when designing schools. We can see repeating trends in the school design. More than once have schools been built that aren’t adequate learning spaces. It seems like architects and stakeholders haven’t learned from previous mistakes, partly because research on school architecture and evaluations of school buildings’ effects on academic performance has been scarce. Children are sensitive to auditory and visual stimulation when trying to concentrate. Most of the strategies are helping the students to focus on the task and avoiding distractors. Strategies that promote good academic achievements should be taken into consideration from the first design step.
Keywords: Learning environment School building Concentration difficulties Pedagogy Education